ПРАВОВИЙ ЗАХИСТ ДІТЕЙ ВІД НАСИЛЬСТВА В СІМ'Ї - Бандурка, Ірина Олександрівна (SUPREMANCE OF LAW, 2018)
The article deals with the system of legal protection of children from violence in the family, which should be carried out by state authorities and local self-government bodies according to various current normative-legal acts. The state at the legislative level should ensure the protection of children from all forms of physical, mental and material abuse, insults, negligent and ill-treated, exploited, abusive practices that may be applied to children by other family members. Ukraine has a deployed system of criminal, civil, and administrative and legal protection of children from domestic violence, but the absence of clear by-laws and the mechanism for their implementation restrains such protection and leads to the widespread nature of the ill-treatment of children. In the article, the forms of prevention of child abuse and the protection of children from domestic violence are proposed to be grouped into three groups: primary, secondary and tertiary, emphasizing the need to strengthen the interaction between state bodies and social services in the field of children’s rights protection and the advisability of making appropriate changes to the current legislation in order to improve the legal protection of children from domestic violence.
Keywords: child; violence; family; help; protection; state bodies